Disruptive technologies for society 5.0 : exploration of new ideas, techniques, and tools - Bali, Vikram; Bhatnagar, Vishal, 1977-; Sinha, Sapna; Johri, Prashant (CRC Press, 2022)
"This book investigates various challenges faced by the Engineering sector concerning disruptive technologies and society 5.0. It explores these technologies in different industries and settings and addresses the challenges and obstacles confronted along with the practical implementation or adoption of them. Disruptive Technologies for Society 5.0: Exploration of New Ideas, Techniques, and Tools highlights the important role of disruptive technologies such as Artificial Intelligence, Internet of Things, Blockchain, and Cloud Computing and the part they play in the current industrial environment. Current research trends in this field as well as case studies are also included. This book is intended for researchers and academicians and will enable them to explore new ideas, techniques, and tools"--